2014
DOI: 10.1074/jbc.m113.506816
|View full text |Cite
|
Sign up to set email alerts
|

Role of Guanine Nucleotide Exchange Factor-H1 in Complement-mediated RhoA Activation in Glomerular Epithelial Cells

Abstract: Background: Disruption of the actin cytoskeleton-dependent structural integrity of glomerular epithelial cells (GEC) leads to glomerular dysfunction. Results: We have identified molecular mechanisms through which the injury-causing complement complex induces cytoskeletal changes in GEC. Conclusion: Complement-induced activation of the ERK/GEF-H1/RhoA pathway protects GEC from cell death. Significance: This study furthers our understanding of mechanisms underlying GEC foot process effacement and functional impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The increase in TEER observed here is somewhat unexpected as pathogenic stimuli are normally associated with a decrease in barrier function. However, sub-lytic C5b-9 has been shown to activate ERK1 and RhoA in various cell types (60, 61), consistent with our observation of ERK1/2 activation by C5b-9 here, and in kidney epithelial cells RhoA activation has been shown to tighten epithelial junctions (62). We also observed that TEER was elevated when C5b-9 was assembled on the apical RPE cell surface (not shown), further supporting the idea that it is the intracellular trafficking of the complex that appears to stimulate the increase in TEER rather than its presence at the cell surface.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in TEER observed here is somewhat unexpected as pathogenic stimuli are normally associated with a decrease in barrier function. However, sub-lytic C5b-9 has been shown to activate ERK1 and RhoA in various cell types (60, 61), consistent with our observation of ERK1/2 activation by C5b-9 here, and in kidney epithelial cells RhoA activation has been shown to tighten epithelial junctions (62). We also observed that TEER was elevated when C5b-9 was assembled on the apical RPE cell surface (not shown), further supporting the idea that it is the intracellular trafficking of the complex that appears to stimulate the increase in TEER rather than its presence at the cell surface.…”
Section: Discussionsupporting
confidence: 91%
“…10 In cultured GECs, MAC-induced ERK-dependent activation of guanine nucleotide exchange factor H1 (GEF-H1), a guanine nucleotide exchange factor, and subsequent RhoA activation, providing a possible mechanism for MAC-induced actin cytoskeleton condensation and podocyte foot effacement in membranous nephropathy. 35 Furthermore, MAC can cause lysosomal membrane permeabilization, blocking fusion of autophagosomes with the lysosome and impairing lysosomal degradation of autophagosomes in podocytes and tubular epithelial cells. 36 MAC also triggers intracellular signaling independent of K þ efflux, leading to inflammasome assembly and subsequent processing and secretion of IL-1b and IL-18.…”
Section: Mac Signaling Initiated Independently Of Ion Fluxmentioning
confidence: 99%
“…62 Complement-induced RhoA activity in rat podocytes were blunted by J o u r n a l P r e -p r o o f GEF-H1 knockdown and this resulted in exacerbated complement-mediated cytolysis. 61 The results suggest that GEF-H1 mediated RhoA activation in podocytes could be cytoprotective in the context of complement-mediated injury such as membranous nephropathy.…”
Section: Arhgef2 (Rho/rac Guanine Nucleotide Exchange Factor 2; Gef-h1)mentioning
confidence: 91%
“…ARHGEF2 (commonly known as GEF-H1) is a dual GEF for RhoA and Rac, although its role as a Rho-GEF is much better characterized. 60 RhoA was activated by complement C5b-9 both in cultured rat podocytes 61 and in glomeruli in the rat model of membranous nephropathy (passive Heymann nephritis). 62 Complement-induced RhoA activity in rat podocytes were blunted by J o u r n a l P r e -p r o o f GEF-H1 knockdown and this resulted in exacerbated complement-mediated cytolysis.…”
Section: Arhgef2 (Rho/rac Guanine Nucleotide Exchange Factor 2; Gef-h1)mentioning
confidence: 99%